Acentuação gráfica na escrita de crianças das séries iniciais - Ney, Luanda Alvariza Gomes (2012)
This research describes and analyses, in data extracted from spontaneous texts, the use of acute accent marks by young primary students. It is debated the relations established, in initial writing, between acute accent marks and children s knowledge about the language prosody. The proposal for attribution of acute accent marks by Bisol (1992, 1994) is the basis of this study. The analyzed corpus is comprised of 3161 words (not verbs) which receive acute accent marks, according to spelling norm, and 222 words where the words received acute accent marks when, according to the norm, it is not necessary. The resulting data were obtained by research made with 987 texts produced by children in two schools, a private and a public in the city of Pelotas/RS. The data were submitted to qualitative and quantitative analysis having into account two categories: correct answers and mistakes. The results demonstrate that: i) the majority of correct answers referring to acute accent marks occur in oxytone words and tonic monosyllables, mainly when the stressed vowels are the medium o and e ; ii) when stressing inadequately, children end up revealing coherent hypothesis related to phonetics and also to language prosody, because, in most of these cases, the acute accent marks, besides coinciding with the tonic syllable of the word, it is used for indicating open vowels; iii) the data of omission of acute accent marks represent 84% of the mistakes registered; iv) when the acute accent mark takes place in the changed syllable, it is verified a tendency in stressing as tonic the penultimate syllable, which characterizes the general rule of prosodic acute accent mark in Portuguese. The data confirm also that the progress in education constitutes an important factor for appropriation of rules of acute accent marks use by young learners, mainly, in private schools. Keywords: acute accent marks, prosodic accent marks, writing acquisition.